Adopting the euro in Central Europe's challenges of the next step in European integration - Schadler, Susan [et al.] (IMF WashingtonUS, 2005)
Identifies the considerations that will mold the accession countries' strategies for adopting the euro. Draws on the experiences of the existing euro-area members, to anticipate issues that will arise in the transition countries. Examines vulnerablities on which IMF surveillance will need to focus during the process of euro adoption.